Pengaruh Tata Kelola Perusahaan, Komite Audit, Dan Kualitas Audit Terhadap Kinerja Perusahaan - Alfio Surya Reynaldi; Cris Kuntadi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Corporate governance, audit committee, and audit quality are important factors that can influence company performance. Good corporate governance can create an effective internal control system, increase transparency and maintain company accountability. The audit committee, as part of corporate governance, plays a role in overseeing the financial reporting process, evaluating the internal control system, and monitoring external audit performance. High audit quality can increase stakeholder confidence in the company's financial reports and provide guarantees for the accuracy and reliability of financial information. This research aims to analyze the influence of corporate governance, audit committee, and audit quality on company performance. Corporate governance variables are measured using corporate governance scores, while audit committee variables are evaluated based on the characteristics and effectiveness of the audit committee. Audit quality is assessed by the reputation and experience of the external auditor. Meanwhile, company performance is measured using financial ratios such as return on assets (ROA) and return on equity (ROE). This research uses data from companies listed on the Indonesia Stock Exchange (BEI) during a certain period. Data analysis was carried out using the multiple linear regression method to test the influence of independent variables on the dependent variable. It is hoped that the findings of this research will contribute to the development of corporate governance practices, audit committee management, and improvement of audit quality in Indonesia, as well as provide insight for companies in efforts to improve their financial and operational performance.